The role of complement in tumor immune tolerance and drug resistance: a double-edged sword - Ronghui Yang; Di Fu; Di Fu; Aijun Liao (Frontiers in Immunology)
The domain of cancer treatment has persistently been confronted with significant challenges, including those associated with recurrence and drug resistance. The complement system, which serves as the foundation of the innate immune system, exhibits intricate and nuanced dual characteristics in the evolution of tumors. On the one hand, the complement system has the capacity to directly inhibit cancer cell proliferation via specific pathways, thereby exerting a beneficial anti-tumor effect. Conversely, the complement system can also facilitate the establishment of an immune escape barrier for cancer cells through non-complement-mediated mechanisms, thereby protecting them from eradication. Concurrently, the complement system can also be implicated in the emergence of drug resistance through a multitude of complex mechanisms, directly or indirectly reducing the efficacy of therapeutic interventions and facilitating the progression of cancer. This paper analyses the role of the complement system in tumors and reviews recent research advances in the mechanisms of tumor immune tolerance and drug resistance.